2014
DOI: 10.1126/science.1256780
|View full text |Cite
|
Sign up to set email alerts
|

Core and region-enriched networks of behaviorally regulated genes and the singing genome

Abstract: Songbirds represent an important model organism for elucidating molecular mechanisms that link genes with complex behaviors, in part because they have discrete vocal learning circuits that have parallels with those that mediate human speech. We found that ~10% of the genes in the avian genome were regulated by singing, and we found a striking regional diversity of both basal and singing-induced programs in the four key song nuclei of the zebra finch, a vocal learning songbird. The region-enriched patterns were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
140
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 105 publications
(149 citation statements)
references
References 109 publications
(81 reference statements)
7
140
0
1
Order By: Relevance
“…Although the distinct transcriptional responses were dominated by neurons collected at days 1 and 7, day 0 neurons were found throughout pseudotime, suggesting that individual cortical neurons engage these plasticity responses in the baseline state. Previous studies showed that averaged responses induced by neural activity measured over hours compared across brain regions or between inhibitory and excitatory neurons exhibit common early transcriptional responses leading to cell-type specific late responses (Spiegel et al, 2014; Whitney et al, 2014). Our single-cell RNA sequencing data reveal that the decision to engage a particular response to experience-dependent plasticity on longer timescales is not intrinsically linked to subtype identity.…”
Section: Discussionmentioning
confidence: 99%
“…Although the distinct transcriptional responses were dominated by neurons collected at days 1 and 7, day 0 neurons were found throughout pseudotime, suggesting that individual cortical neurons engage these plasticity responses in the baseline state. Previous studies showed that averaged responses induced by neural activity measured over hours compared across brain regions or between inhibitory and excitatory neurons exhibit common early transcriptional responses leading to cell-type specific late responses (Spiegel et al, 2014; Whitney et al, 2014). Our single-cell RNA sequencing data reveal that the decision to engage a particular response to experience-dependent plasticity on longer timescales is not intrinsically linked to subtype identity.…”
Section: Discussionmentioning
confidence: 99%
“…Approximately 30% (22/73) of the differentially expressed genes that were detected in our study (including SNCA ) belong to the gene families that have been shown to contribute significantly to shared gene expression specializations in the brains of humans and song-learning birds (Table S5). Another recent study by Whitney et al55 analyzed the genome-wide singing-regulated gene expression across time in four major brain regions of songbirds and reported a total of 1883 singing-regulated genes, with FOS being the most significant gene. Several genes that were differentially expressed here after music performance ( FOS, PLIN5, ODC1, DUSP1, FBXO7, HIST2H2BE, DOPEY2, and PHAX ) have also been reported by Whitney et al to be regulated by singing in songbirds.…”
Section: Discussionmentioning
confidence: 99%
“…A large group of papers used the bird genomes to investigate a key feature of general genome evolution: transposable and endogenised retroviral elements (Chong et al 2014;Cui et al 2014;Suh et al 2014a, b). Finally, one of the most eminent traits of birds, the ability of multiple lineages to sing and especially learn songs, was studied in a multifaceted way by comparative genomics (Whitney et al 2014;Wirthlin et al 2014), transcriptomics (Pfenning et al 2014;Wang et al 2014b), and candidate gene approaches (Wang et al 2014b). …”
Section: A First Phylogenomic Avian Tree Of Lifementioning
confidence: 99%